ENVIRONMENTAL IMPACTS ON INFORMAL SETTLEMENTS ASCRIBED TO IMPROPER WASTE MANAGEMENT IN KABUL - Mohamad Husny, Zuhra Junaida binti Mohamad Husny; Ibrahimy, Rahmatullah (Journal of Architecture, Planning and Construction Management, 2022)
This study focuses on ensuring a sustainable and livable environment in the 8th district informal settlement of Kabul. It seeks to look at the environmental impacts of improper waste management on informal settlement in Kabul city. The study analyses current waste management situation and challenges and environmental effects on informal settlers in the city. A qualitative methodology approach with direct observation and interview were used for data collection. A total of three experts was interviewed from relevant authorities, and purposive sampling used for selecting respondents. Thematic and template analysis techniques were used for data analysis. The findings of this study revealed that waste management situation was not frequent; lack of infrastructure and facilities, poverty, rapid urbanization, lack of municipality technical capacity, funds, and experts were the main factors to improper waste management. Waste was not collected correctly due to weak accessibility and imperfect nature of roads. Waste burning for house heating in winter and residents of informal settlements were not aware of considering environmental and health issues. Improper waste management creates severe environmental impacts such as land and water pollution, air pollution, infectious diseases, unpleasant smells, drains blockage, and loss of biodiversity. The study concluded with suggestions that infrastructure must be improved, residents should be educated about environment protection, municipality contribution, and community contribution should be ensured as well as a sustainable redevelopment model is suggested to eradicate informal settlement and ensure a sustainable environment. Findings will serve as the basis for information that policymakers should concentrate on when planning a course of action or inaction to improve the waste management systems in informal settlements.